Transmethodological mo(ve)ments : Creating a third space for emancipatory research - Khawaja, Iram; Mørck , Line Lerche (Outlines. Critical Practice Studies, 2022)
This article presents the authors’ collaboration with a former gang leader, referred to as X, as part of a research project exploring identity transformation and mo(ve)ments beyond gang engagement. The project is based on a transmethodological approach that involves different embodied researcher positionalities, theoretical engagements, and a merging of diverse research fields. The exploration of the different movements and changes in X’s life is based on, what we call a transmethodological mo(ve)ment ethnography, exploring mo(ve)ments of transformation of identity, engagement and community in the everyday life of X, who is striving to become a good, practicing Muslim. This approach makes it possible to go into depth with key moments of change in a subject’s life and pursue them from different theoretical perspectives by integrating and transgressing concepts, analytical gazes and positionalities. To analyze and understand the former gang leader’s life and process of transformation, we utilize poststructuralist and decolonial theory and integrate these approaches with those of social practice theory and critical psychology. In this article, we examine how we as researchers can transverse different theoretical and embodied positionings, analyzing transmethodology as closely linked to the positioning of the researcher, and ultimately pointing towards an emancipatory form of research practice.